Project Scheduling Analysis With CPM PERT Method (Case Study on Tasikmalaya City Swasana Village Restaurant Project) - Delfi Santika; Suci Putri Lestari; Barin Barlian (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the analysis of project scheduling using the Critical Path Method (CPM) Program Evaluation and Review Technique (PERT) method in the Tasikmalaya Swasana Village Restaurant project. The method used in this study is a qualitative descriptive method. By taking data on all activities and costs needed for the construction of a self-financing village restaurant. The data collected is in the form of primary data and secondary data. Data analysis in this study used POM for Windows QM Version 5. The results of the research from project scheduling using the Critical Path Method (CPM) method can be completed for 29 weeks with a total cost needed of Rp. 1,606,633,852. while using the Program Evaluation and Review Technique (PERT) method which analyzes using three estimated times can find out the possibility that the project can be completed within 38 weeks with a success rate of 99% and the total cost that it takes Rp. 1,606,633,852.